Peningkatan Kinerja Bisnis Melalui Integrasi Internet of Things (IoT) Pada Supply Chain Management (SCM) - Putra, Defriko Gusma (Jurnal Marketing, 2024)
The role of the Internet of Things (IoT) is increasingly important in supporting the automation of regular processes and operational decision making in Supply Chain Management (SCM). The implementation of IoT technology with extensive wireless sensor networks (WSN) allows direct access to the sensor center and sensing capabilities of devices connected to the internet. This technology collects large amounts of data through wide area data communication networks. Networks that can respond dynamically in SCM to changes triggered by IoT-based infrastructure. The increasing use of technology raises challenges related to integration failures and data privacy issues. The method used in this study is descriptive qualitative which presents a systematic review of improving business performance through IoT integration in SCM. This study is expected to provide insights and solutions related to improving business performance through IoT integration in SCM. IoT is the right choice to be integrated into SCM with its various advantages and disadvantages, IoT is one of the best choices in work activities and data integration processes and all processes in the supply chain so that it will ultimately have an impact on improving business performance and efficiency. Keywords: Business Performance, Internet of Things (IoT), Supply Chain Management (SCM).